Quick Response codes for virtual learner evaluation of teaching and attendance monitoring - Mo, Roxana; Wright, Emily; MacGarrow, Iain; Pathak, Sangeeta (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Monitoring attendance and obtaining timely learner evaluations for virtual teaching sessions can be challenging. At our Obstetrics and Gynecology webinar programme, we have utilised Quick Response (QR) codes this purpose. Following each session, attendees scan an on-screen QR code which links to an online evaluation form and registers their attendance. Feedback can therefore be obtained quickly, is scalable to large participant numbers and is securely stored in digital format. QR reader applications are widely available and cost-free, which makes this technique accessible for learners. Using QR codes for teaching evaluation is simple and could be adopted across many educational applications.